PERSEPSI GURU PENDIDIKAN JASMANI SEKOLAH DASAR TERHADAP PENDEKATAN TEMATI K INTEGRATI F PADA KURIKULUM 2013 - Subagyo, Amat Komari dan Aris Fajar Pambudi (Jurnal Pendidikan Jasmani Indonesia, 2015)
AbstractThis research was motivated by the understanding that has not been the same for thematic integrative approachto the curriculum 2013. This research aimed to determine how the perception of physical education teachers forelementary school of thematic integrative approach to curriculum 2013. This research design was a descriptive study.The method used in this study was by survey method. The population in this researchwas all physical educationsteacher for elementary school in Yogyakarta Special Region. The samples in this study were 46 teachers. The samplingtechnique used was purposive sampling. The data collection technique was with questionnaire. The data analysistechnique was with descriptive percentage. The result results showed that the perception of physical educationteachers for elementary school of thematic integrative approach to curriculum 2013 in sequence as follows: verygood perception was at 4.4%, good perception was 23.9%, medium perception was at 32.5%, the less perceptionwas 19.6%, and not good perception was 19.6%.Keywords: Perception, Physical Education Teachers for Elementary School, Integrative Thematic ApproachAbstrakPenelitian ini dilatarbelakangi oleh pemahaman yang belum sama terhadap pendekatan tematik integratif padakurikulum 2013. Penelitian ini bertujuan untuk mengetahui bagaimana Persepsi Guru Pendidikan Jasmani SekolahDasar terhadap Pendekatan Tematik Integratif pada Kurikulum 2013. Desain penelitian ini adalah penelitian deskriptif.Metode yang digunakan adalah metode survei. Populasi penelitian adalah seluruh Guru Pendidikan Jasmani SekolahDasar di Daerah Istimewa Yogyakarta. Besar sampel yang digunakan adalah 46 guru. Teknik pengambilan sampelmenggunakan purposive sampling. Teknik pengumpulan data dengan angket. Teknik analisis data dengan statistikdeskriptif persentase. Hasil penelitian menunjukkan bahwa Persepsi Guru Pendidikan Jasmani Sekolah Dasarterhadap Pendekatan Tematik Integratif pada Kurikulum 2013 secara berurutan sebagai berikut: persepsi sangatbaik sebesar 4.4%, persepsi baik sebesar 23.9%, persepsi cukup sebesar 32.5%, persepsi kurang baik sebesar19.6%, dan persepsi tidak baik sebesar 19.6%.Kata kunci: Persepsi, Guru Penjas Sekolah Dasar, Pendekatan Tematik Integratif